Global transcriptional analysis of human FHs 74 Int intestinal epithelial cells after exposure to advanced glycation end products - Katharina Schwertner; José Basílio; Karin Hoffmann-Sommergruber; Isabella Ellinger; Sabine Geiselhart (PLoS ONE, 2025)
Advanced glycation end products (AGEs) and reactive intermediates, such as methylglyoxal, are formed during thermal processing of foods and have been implicated in the pathogenesis of a series of chronic inflammatory diseases. AGEs are thought to directly interact with the intestinal epithelium upon ingestion of thermally processed foods, but their effects on intestinal epithelial cells are poorly understood. This study investigated transcriptomic changes in human intestinal epithelial FHs 74 Int cells after exposure to AGE-modified human serum proteins (AGE-HS), S100A12, a known RAGE ligand, and unmodified human serum proteins (HS). In contrast to previous studies employing cancer cell lines, RNA sequencing of FHs 74 Int cells treated with AGE-HS did not reveal transcriptional changes associated with increased proliferation, increased expression of tight junction proteins or proinflammatory responses. Surprisingly, neither AGE-HS nor S100A12 treatments resulted in significant differential gene expression at standard analysis thresholds, while unmodified HS induced minor transcriptional changes. Gene set enrichment analysis revealed that AGE-HS treatment induced downregulation of gene sets linked to MYC, interferon responses, and oxidative phosphorylation, as well as pathways related to neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s disease, paralleling some effects observed with S100A12. This is the first global transcriptomic analysis of FHs 74 Int cells and the first unbiased investigation of signaling pathway alterations in intestinal epithelial cells exposed to AGEs. In contrast to previous studies, this analysis did not reveal any significantly differentially expressed genes, thus challenging previous reports of robust AGE-induced inflammatory and proliferative effects and emphasizing the importance of an isolated experimental setting and rigorous endotoxin testing.